Knowledge relationship and pupils’ practices: the notion of alternative games - Rilhac, Patrice (Swiss Journal of Educational Research, 2018)
This article presents the results of a study whose ambition is to compare students’ relationship to knowledge when they are confronted with the following specific knowledge: demonstrating in mathematics, and climbing in physical education and sports. Our methodological approach relies on the notion of «methodological algorithm». Results show the existence of different forms of games we say alternative, because they are not the form of epistemic games expected by teachers.